The Impact of Product Innovation and Product Quality on Supermi Repurchase Decisions - Arianto, Fachrizal; Aminah, Siti (Journal of Applied Business, Taxation and Economics Research, 2025)
The food and beverage industry in Indonesia has experienced rapid growth, driven by increasing consumer demand and evolving market dynamics. As one of the world’s largest instant noodle-consuming countries, Indonesia presents a highly competitive environment for food brands. In this context, product innovation and consistent product quality are crucial for maintaining consumer loyalty and securing a long-term market position. Supermi, a long-established instant noodle brand, faces intense competition from newer and more innovative brands. To remain competitive, it is essential for Supermi to understand the factors influencing consumer repurchase behavior. This study aims to analyze the influence of product innovation and product quality on repurchase decisions, using Supermi as a case study. A quantitative research method with a descriptive approach was applied, involving 95 respondents selected through random sampling. The research was conducted among students of the Management Study Program, Faculty of Economics and Business, Universitas Pembangunan Nasional “Veteran” East Java. Data were collected through an online questionnaire distributed via Google Forms and analyzed using SmartPLS 3.0. The results show that both product innovation and product quality play an important role in encouraging repurchase decisions. These findings highlight the need for continuous product development and quality assurance to enhance customer retention in a highly saturated market.